(untitled) (Ameghiniana, 2013)
PALYNOLOGICAL STUDlES OF THE BAQUERÓ FORMATION (CRETACEOUS), SANTA CRUZ PROVINCE, ARGENTINA,III. - Six spore species, which belong to already known taxa are here descríbed: three species of Trilobosporites, one of Rouseisporites, Taurocusporites and Sestrosporites. All of these but two are known to occur in Australia (and other regions) in homotaxial strata. Trilobosporites apioerrucatus Couper, is known only from Lower Cretaceous strata of Europe and Canada, while Taurocusporites segmentatus Stover has been recorded in the Lower Cretaceous of Cariada and U.S.A. The geographio extension of these two species to southern regions is therefore established.